Corporate Social Responsibility along the global value chain - Philipp Herkenhoff; Sebastian Krautheim; Finn Ole Semrau; Frauke Steglich (Journal of Development Economics, 2024)
Locating substantial parts of the production process in developing and emerging economies, many firms face an increasing demand by stakeholders for Corporate Social Responsibility (CSR) along their value chains. Contractual incompleteness between firms and their suppliers at different stages of production can exacerbate the ability to meet these demands. We analyze a model of sequential production with incomplete contracts where CSR by independent suppliers differentiates the final product in the eyes of caring consumers. Progressing down the value chain, our model predicts an increasing CSR profile from upstream suppliers with low CSR to downstream suppliers with higher CSR. We confirm this prediction using Indian firm-level data – computing a firm's value chain position by combining its product-level sales information with the World Input–Output Database. We find that more downstream firms report higher CSR expenditures as measured by a combination of staff welfare spending and social community spending.
https://github.com/FraukeSteglich/CSR-along-the-GVC
Keywords: F12; F61; F63; L23; M14; O12; 330; Corporate Social Responsibility; Global value chains; Incomplete contracts; Sustainable development; Ethical sourcing; India